Al Kawakib al Nayyirat fi ma'rifah min Ikhtalat min al Rawah al-Thiqat - Muhammad ibn Ahmad Ibn Muhammad al Khatib Ibn al Barkah al Ma'ruf bi Ibn-al-Kiyali (Dar al Kutub al 'Ilmiyyah, 1987)
ws.c.1/stoc6, c.1